Assessing health, quality of life and urogenital function in a sample of the Swedish general population: a cross-sectional study. Issue 5 (5th May 2018) - Bock, David; Angenete, Eva; Gonzales, Elisabeth; Heath, Jane; Haglind, Eva
Abstract : Objective: Evaluate the urinary, bowel and sexual function as well as stress symptoms and depression in a sample of the Swedish population. Design: A random sample of Swedish men and women in age groups from 30 to 89 years, a total of 3000 individuals, were contacted and after receiving informed consent, a questionnaire was sent. Main outcome measures: Measures of urinary, bowel, sexual function and quality of life. Results: The questionnaire was sent to 2094 individuals who gave informed consent. The questionnaire was answered by 1078 individuals. Quality of life, stress symptoms and depressed mood were relatively constant across age groups for both men and women. Urinary function differed significantly across gender and age groups, but bowel function was relatively unaffected by age. Overall bowel dysfunction was slightly more prevalent among women compared with men. For both men and women, the frequency of intercourse or other sexual activities decreased with age, whereas sexually associated distress increased by age in men, but decreased among women. Conclusions: In a general population, the urinary function varied across age and sex. Overall bowel dysfunction was slightly more prevalent among women compared with men. Sexually associated distress increased by age for men, but decreased for women. Trial registration number: NCT02392923 ; Results.